2001
DOI: 10.2337/diabetes.50.2.404
|View full text |Cite
|
Sign up to set email alerts
|

Protection Against Oxidative Stress—Induced Insulin Resistance in Rat L6 Muscle Cells by Micromolar Concentrations of α-Lipoic Acid

Abstract: In diabetic patients, ␣-lipoic acid (LA) improves skeletal muscle glucose transport, resulting in increased glucose disposal; however, the molecular mechanism of action of LA is presently unknown. We studied the effects of LA on basal and insulin-stimulated glucose transport in cultured rat L6 muscle cells that overexpress GLUT4. When 2-deoxy-D-glucose uptake was measured in these cells, they were more sensitive and responsive to insulin than wild-type L6 cells. LA, at concentrations ≤1 mmol/l, had only small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
243
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(262 citation statements)
references
References 53 publications
(62 reference statements)
17
243
0
2
Order By: Relevance
“…Mitochondrial ROS release and the effect of training Previous studies have suggested that increased cytosolic concentration of free radicals have an inhibitory effect on the insulin signalling cascade [16]. A main purpose of the present study was to investigate the hypothesis that insulin resistance is associated with increased mitochondrial ROS release.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Mitochondrial ROS release and the effect of training Previous studies have suggested that increased cytosolic concentration of free radicals have an inhibitory effect on the insulin signalling cascade [16]. A main purpose of the present study was to investigate the hypothesis that insulin resistance is associated with increased mitochondrial ROS release.…”
Section: Discussionmentioning
confidence: 92%
“…In cultured cells there is experimental evidence that ROS have an inhibitory effect on insulin signalling [16,17]. Human studies have shown that obesity and high-fat diet increase mitochondrial hydrogen peroxide release [18].…”
Section: Introductionmentioning
confidence: 99%
“…The biological responses of various cultured cells to insulin have been shown to be impaired by micromolar H 2 O 2 concentrations [29±32, 39]. In cells representing the metabolic target tissues of insulin such as 3T3-L1 adipocytes, this effect of oxidative stress causes insulin resistance, including impaired insulin-stimulated glucose uptake activity [29,30,39]. The mechanisms underlying this phenomenon appear to be complex and depend on the duration and intensity of the oxidative insult.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative/nitrosative stress may have a serious impact on cell viability and induce cellular responses leading to cell death (3). Many studies have shown a connection between oxidative molecular damage and pathophysiological mechanisms associated with severe diseases such as atherosclerosis (4), neurodegenerative disorders (5), and diabetes, and an important role in the etiopathogenesis of inflammatory diseases (6). There is also a relationship between oxidative stress and aging processes (7).…”
Section: Introductionmentioning
confidence: 99%